UI/UX Design of Ineffable Psychological Counseling Mobile Application Using Design Thinking Method - Defriani, Meriska; Lintang Nuril Islami; Teguh Iman Hermanto (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Application design is one of the important things in application development because the application that has a bad design will cause discomfort and confusion for users, especially in health applications, which have their own difficulties where application design must focus on what users need to be easy to understand, especially mental health application because there are still few application for mental health or self-care even though since the pandemic, mental health problems have increased drastically, this makes many people seek help in mental help. Design thinking is a method used to solve a problem where the solution comes from that user’s experiences or needs. The Design Thinking method consists of five stages: Empathize, Define, Ideate, Prototype, and Test. In the test step, testing was carried out using the Cognitive Walkthrough method with the help of the Maze tool with a learnability value of 97%, an error rate of 0.04, time-based efficiency of 0.05 task/second, and the MIUS value of each task were obtained a fairly high value indicating that design prototype is easy to use, easy to understand and efficient. While the MAUS score got a score of 94, which was included in the high level, indicating that the interface design was feasible to be implemented.